2014
DOI: 10.1016/j.appet.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Young children's food brand knowledge. Early development and associations with television viewing and parent's diet

Abstract: Publication informationAppetite, 80 (1) : 197-203 Publisher Elsevier Item record/more information http://hdl.handle.net/10197/5641 Publisher's statementThis is the author's version of a work that was accepted for publication in Appetite. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Of interest for research in advertising effects is the contrast between the free and prompted recall rates found. Reflecting findings for much younger children [84], this indicates that even when memory is more developed in adolescence, free recall remains a poor measure of advertising exposure compared to prompted recognition. Future areas of exploration are links between social responses to food marketing (sharing and peer assessment) and consumption patterns.…”
Section: Implications For Research and Policymentioning
confidence: 82%
“…Of interest for research in advertising effects is the contrast between the free and prompted recall rates found. Reflecting findings for much younger children [84], this indicates that even when memory is more developed in adolescence, free recall remains a poor measure of advertising exposure compared to prompted recognition. Future areas of exploration are links between social responses to food marketing (sharing and peer assessment) and consumption patterns.…”
Section: Implications For Research and Policymentioning
confidence: 82%
“…The strong pull toward food brands starts early. By 5 years of age, most children can name common food brands and more accurately name unhealthy brands than healthy brands (Tatlow‐Golden, Hennessy, Dean, & Hollywood, ). Federal regulation is unlikely to be effective in the United States because concerns about paternalism and freedom of speech outweigh concerns about children's health.…”
Section: A Cells‐to‐society Approach To Childhood Obesitymentioning
confidence: 99%
“…The study by Tatlow-Golden et al (2014) dealt with the development of 2-to-5-yo children’s brand knowledge of healthy and unhealthy foods, which had been highly advertised on television, as a predictor of food request, purchase, and consumption. They found that brand knowledge increased from 3 to 5 years and that 4-yo children showed significantly greater brand knowledge than 3-yos.…”
Section: Children’s Stage Of Cognitive Development and Vegetable Consmentioning
confidence: 99%
“…Parent eating and children’s age were, however, found to be independent predictors of children’s knowledge of unhealthy brands. Therefore, children’s brand knowledge and its effects develop earlier (between 3 and 4 years) than children’s understanding of food healthfulness and its effects (between 4 and 5 years) ( Tatlow-Golden et al, 2014 ). One of the effects of young children’s knowledge of brands offering high sugar-content products, and therefore unhealthy foods, refers to increases in their body mass index, as found by Cornwell et al (2014) in 3-to-6-yo children.…”
Section: Children’s Stage Of Cognitive Development and Vegetable Consmentioning
confidence: 99%